EPISTEME PLATO DAN ARISTOTELES: ANALISIS KOMPARATIF IDEALISME DIALEKTIS VERSUS SILOGISME EMPIRIS DALAM FILSAFAT ILMU - Ray, Ibrahim Hasan (Sanjiwani: Jurnal Filsafat, 2026)
This article offers a comparative analysis of the concept of episteme in the thought of Plato and Aristotle, aiming to reveal each method's contributions to the development of scientific knowledge, clarifying their roles in formulating and testing scientific truth, and exploring implications for contemporary knowledge advancement. Employing a qualitative-interpretative approach through textual and comparative analysis of Plato's Socratic dialogues and Aristotle's logical works, the study highlights Plato's reflective-transcendental dialectical idealism against Aristotle's systematic-deductive empirical syllogism. Key findings demonstrate their foundational ontological-epistemological differences: Plato grounded in the eternal World of Ideas, Aristotle in concrete hylomorphic reality, giving rise to two scientific paradigms: reflective-normative (mathematics, ethics) versus empirical-descriptive (natural and social sciences). These approaches complement each other in shaping a holistic contemporary scientific paradigm that integrates philosophical and empirical dimensions. In conclusion, the article asserts that idealism and syllogism are mutually reinforcing methods for cultivating critical, systematic, and reflective reasoning in scientific inquiry, with their synergy essential for developing a more comprehensive knowledge framework in the modern era, particularly in bridging philosophical and empirical pursuits of scientific truth.